Improved Air Quality Testing Using Kalman Filter Based on IoT Data Fusion for Smart Cities. Issue 1 (May 2021) - Vadivelu, R; Santhakumar, G; Boopana, V P; Dharani, S.; Bharathi, S Dhivya; Balasubramaniam, D
Abstract: Monitoring the amount of gases in air in smart cities provides immature gas emissions, polluting concentrations and filtering are examined in this paper. Air contamination is a worry in numerous metropolitan territories and is a critical reason for respiratory issues for some individuals. Monitoring the quality of air aids in the prevention of emission of gases and also the reduction of disease caused by pollution. A System has been developed to measure the values of CO2, NH3, and CH4 gases and therefore the parameters are sent via the ESP8266 Wi-Fi module through which we can monitor the concentration of the gases by tracking the IP address via IoT and also implemented a Kalman filter which purify the polluted air.